Objective and subjective evaluation of voice quality in patients with chronic Obstructive pulmonary disease (COPD) - Nik Fariza Husna, Nik Hassan (2008)
TITLE: Objective and subjective evaluation of voice quality in patient with chronic obstructive pulmonary disease (COPD). OBJECTIVE: METHOD: RESULT: To test the null hypothesis that there is no difference in voice quality between COPD group with the control group. Subjects were 40 adult participants. Recruited 20 participants in COPD group and control group of 20 participants, with the mean age of 68.95 and 58.40 respectively. Both group underwent Vocal Symptoms Questionaire interview, Peak Expiratory Forced Rate (PEFR) test, voice recording and ear, nose and throat examination. The voice was recorded and analyzed with Dr Speech's Vocal Assessment Version 4 {Tiger DRS,US). The mean COPD and control group were subjected to Mann-Whitney test and descriptive analysis. Vocal Symptom Questionaire showed the mean total vocal symptom were significantly greater in COPD group (18.35 + 9.8) than for the control group (4.65+ 8.5; P<O.OOl). The mean of X Ill CONCLUSION: PEFR were greater for the control group (438.50+ 139.79) than for COPD group (287.80 + 123.11; P<0.001). The vocal assessment were analyzed in term of jitter, shimmer, harmonic to noise ratio (HNR) and maximum phonation time. All the vocal assessment profile mean were more than the normal value and the Mann Whitney test were not significant (P >0.001). Full ENT examination did not reveal any significant finding. The laryngeal and ENT examination also shows no significant pathology to contribute to the voice change in study participant. In the subjective analysis, the null hypothesis is rejected. COPD patients do complain of voice problem but the vocal assessment did not prove the dysphonia claimed by the study group.